The Fiat Fiasco: the insidious erosion of Maqasid of Shari’ah and practical alternatives - Mohamad, Azhar (2015)
In the backdrop of recent financial crises and currency fallouts in the global market, a lot of focus in academia and popular media has shifted towards a re-examination of efficacy of fiat monetary system. While the competence of the endemic system is contentious to utilitarian economists and pragmatists, the tawhidic (monotheistic) paradigm of Islamic Shari’ah demands a more absolutist scrutiny of the validity of such a monetary system in the first place. Notwithstanding this system’s perilous proximity to elements of riba and resultant socio-economic ills, the paper challenges the legitimacy of the fiat system at the definitional, axiological, moral, and Shari’ah levels. To this effect, we outline a brief survey of the historical attempts and success rates (failure rather) of fiat and paper currency experiments around the globe, the salient arguments for and against it (along with our rebuttals), the threats it poses to Islamic ideals, as well as its ceaseless jeopardization of Maqasid (objectives) of Shari’ah. While not decrying the utopian vision of Gold and Silver currencies, the paper contributes to existing theory in line with the Islamic concept of tadarruj (gradualism), as we propose presently plausible “intermediate” alternatives to the fiat system, particularly in payment mechanism area, keeping in mind an ultimate goal of cementing a monetary system fully congruent with the Maqasid of Shari’ah